1997
DOI: 10.1093/bja/78.5.570
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic conditions enhancing gas embolism after venous injury during laparoscopy: a study in pigs

Abstract: This study was designed to determine the conditions that promote carbon dioxide embolism after venous injury during laparoscopy in pigs. Injury to an iliac vein was filmed during laparoscopy in the presence of a pneumoperitoneum created at increasing pressures from 0 to 30 mm Hg in 5-mm Hg increments. At intraperitoneal pressures less than 20 mm Hg, there was a parallel increase in femoral venous pressures, resulting in haemorrhage, with persistent blood flow to the inferior vena cava. At intraperitoneal press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
31
0
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 20 publications
3
31
0
3
Order By: Relevance
“…Nevertheless, our results confirm the findings of Bazin and Dion [15,16]. Laparoscopy with either carbon dioxide or helium and an intra-abdominal pressure of 15 mmHg did not cause significant changes in cardiopulmonary functions or obvious gas embolism.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Nevertheless, our results confirm the findings of Bazin and Dion [15,16]. Laparoscopy with either carbon dioxide or helium and an intra-abdominal pressure of 15 mmHg did not cause significant changes in cardiopulmonary functions or obvious gas embolism.…”
Section: Discussionsupporting
confidence: 90%
“…Unfortunately, helium was not investigated in this experiment. Bazin et al [16] demonstrated that injury of the iliac vein during laparoscopy with CO 2 caused no intravenous gas penetration at intraperitoneal pressures lower than 20 mmHg, while higher pressures led to detectable gas bubbles in the iliac vein. Thus, vessel injury during laparoscopy and elevated intraperitoneal pressure of 15 mmHg does not automatically cause venous gas embolism.…”
Section: Discussionmentioning
confidence: 99%
“…Continuous addition of insufflated air is hypothesized to create conditions favorable for venous air embolism by increasing intraluminal pressure. 20,22,24 Interestingly, the use of specific gas types during endoscopy or laparoscopy has been the subject of debate. 22 Currently, almost all laparoscopy is performed using carbon dioxide due to its properties as a noncombustible, commonly available gas with high aqueous solubility.…”
Section: Discussionmentioning
confidence: 99%
“…Even in laparoscopic surgery, in which large intra-abdominal vessels may be directly exposed to insufflation gas under pressure, venous gas embolism occurs in fewer than 1 of 7,500 cases [3,18,20,22]. Gas embolism during endoscopy is an even rarer event.…”
Section: Discussionmentioning
confidence: 99%